Innovative Approaches to Medical and Pharmaceutical Care, Pharmacotherapy, and Availability of Pharmaceutical Supplies for Tuberculosis Patients in Wartime - Shapovalova, Viktoriia (SSP Modern Pharmacy and Medicine, 2025)
This article explores advanced methodologies for delivering medical and pharmaceutical care to tuberculosis patients under regional wartime conditions. Emphasizing organizational, legal, clinical, and pharmacological considerations, the discussion highlights the critical role of robust pharmaceutical management, enhanced access to anti-tuberculosis medications, and socially oriented logistical protocols for pharmaceutical provisioning and pharmacotherapy. The authors investigate how new pharmacotherapy models can be economically effective, and they propose a series of legal and managerial adaptations tailored to the realities of wartime. By focusing on strategies to secure reliable medication access and implement efficient clinical pathways, this study underscores the importance of a coordinated, multidisciplinary response. Particular attention is paid to the issues of organizational and legal, clinical and pharmacological, pharmaceutical management, increasing the availability of anti-tuberculosis drugs, socially oriented and accessible logistical algorithms for pharmaceutical provision and pharmacotherapy. Moreover, it offers insights into how healthcare systems can remain resilient in crisis situations, ensuring that individuals with tuberculosis continue to receive necessary interventions despite the challenges posed by conflict conditions. Recommendations include revising regulatory frameworks and optimizing pharmaceutical management to meet the specific demands of wartime environments.